2016
DOI: 10.1016/j.medici.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Dobutamine-stress echocardiography speckle-tracking imaging in the assessment of hemodynamic significance of coronary artery stenosis in patients with moderate and high probability of coronary artery disease

Abstract: Left ventricular strain and strain rate analyses during DSE can be used in the assessment of hemodynamic significance of coronary artery stenosis in patients with moderate and high risk for CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 26 publications
1
19
0
5
Order By: Relevance
“…Echocardiography [23] An echocardiography might be performed as a stress test under physical exercise or under concomitant administration of medication such as dipyridamole or dobutamine. This procedure might reveal areas in the left ventricle (LV) with wall abnormalities or hypocontractility.…”
Section: Procedures Explanationmentioning
confidence: 99%
“…Echocardiography [23] An echocardiography might be performed as a stress test under physical exercise or under concomitant administration of medication such as dipyridamole or dobutamine. This procedure might reveal areas in the left ventricle (LV) with wall abnormalities or hypocontractility.…”
Section: Procedures Explanationmentioning
confidence: 99%
“…Since Voight et al, [ 37 ] demonstrated that strain rate analysis during SE provides objective evidence of ischemia, the interest of using quantitative assessment of LV systolic function by 2D speckle tracking during SE gained interest because it removes the subjective nature of visual assessment by wall motion analysis (WMA) in detecting CAD. Hence, a number of studies have shown that imaging GLS% was as good as [ 38 ], [ 39 ] or even superior [ 37 ], [ 40 ] [ 41 ] to conventional echocardiography, subsequently lot of them concluding that GLS% provides incremental diagnostic accuracy in combination with expert WMA [ 42 ] in detecting CAD. Our results were partly in line with such conclusions; however only WMSI appeared as independent predictor of CAD which was consistent with the results of dobutamine SE study of Celutkiene et al, [ 43 ] who stressed that none of the single quantitative parameters investigated was able to identify significant CAD with a comparable diagnostic accuracy vs visual assessment using WMA.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies determined the diagnostic value of speckle-tracking echocardiography in derived myocardial deformation parameters at rest and during stress, can evaluate hemodynamically signifi cance in coronary artery stenosis on those patients with moderate and high probability of CAD. Also, it showed that left ventricular strain and strain rate analyses during DSE can be used in the assessment of hemodynamic signifi cance in coronary artery stenosis, with patients that have moderate and high risk for CAD, with good accuracy [27,28]. One the strategies proposed by Mathias et al [17], to improve DASE sensitivity was the rapid injection of metoprolol in the stress peak with acquisition of post-metoprolol images in maximum range of three minutes.…”
Section: Diagnostic Value and Prognosis Of Dobutamine-atropine Stressmentioning
confidence: 99%